2022
DOI: 10.3389/frsc.2022.1039710
|View full text |Cite
|
Sign up to set email alerts
|

Phytoremediation potential of indoor plants in reducing air pollutants

Abstract: Indoor air quality (IAQ), specifically after the COVID-19 pandemic, has become an international issue, as humans spend 80–90% of their time in indoor microenvironments. Poor IAQ has been related to the sick-building syndrome, nasal and ocular irritations, allergies, and respiratory dysfunction, including premature deaths. Phytoremediation is a novel strategy to absorb, adsorb, assimilate or transfer/reduce air pollutants and improve the IAQ using plants. Hence, the current review aims to explore indoor plants'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 98 publications
0
2
0
Order By: Relevance
“…Research by Maki et al [62] indicates that pets indeed impact indoor microbial diversity, with animal fur, feces, and fleas potentially contributing to increased indoor air microbial contamination [63]. Ravindra et al [64] have found that indoor plants can absorb and process indoor pollutants, reducing toxicity, significantly improving indoor environmental comfort and air quality.…”
Section: Sources Of Bioaerosolsmentioning
confidence: 99%
“…Research by Maki et al [62] indicates that pets indeed impact indoor microbial diversity, with animal fur, feces, and fleas potentially contributing to increased indoor air microbial contamination [63]. Ravindra et al [64] have found that indoor plants can absorb and process indoor pollutants, reducing toxicity, significantly improving indoor environmental comfort and air quality.…”
Section: Sources Of Bioaerosolsmentioning
confidence: 99%
“…To overcome the above limitations, biological air remediation using plants and microorganisms (phytoremediation) has drawn attention recently [17][18][19]. For example, in the phytoremediation that uses the metabolic ability of living plants to catabolize and detoxify contaminated compounds [20], Sansevieria (Snake plant) can absorb CO 2 at ~0.49 ppm/m 3 [21], and, in a closed chamber (1 m 3 ), house plants can reduce CO 2 to 17~24% [22], up to 51~77% by combining ventilation [23].…”
Section: Introduction 1background Problems In Indoor Co 2 Mitigationmentioning
confidence: 99%